Positive impacts of typical desert photovoltaic scenarios in China on the growth and physiology of sand-adapted plants - Meng, Ruibing; Meng, Zhongju; Ren, Xiaomeng; Cai, Jiale; Tong, Xufang (Frontiers in Plant Science, 2025)
Desert regions are characterized by complex terrain, frequent wind–sand activities, and extreme environmental conditions making vegetation recovery after disturbances difficult. The construction of large-scale photovoltaic (PV) power stations presents a significant challenge in balancing with vegetation protection. This study focused on a large PV site in the Hobq Desert examining the growth characteristics of Astragalus adsurgens at different positions within fixed PV arrays. It also analyzed changes in chlorophyll (Chl), soluble sugar (SS), soluble protein (SP), enzyme activity, and other physiological indicators to evaluate the plant’s adaptive mechanisms to the presence of PV panels. The results showed that A. adsurgens near the PV panels exhibited significant growth advantages, with plant height, leaf length, and stem–leaf nutrient content greater than the those of the control (CK) showing an adaptive trend of elongation, thinning, and enlargement. During the growing season, A. adsurgens located before, behind, and under the panels increased Chl with environmental changes. The plants also adjusted their SS, SP, and other internal substance levels depending on their location relative to the panels. Notably, superoxide dismutase (SOD) and peroxidase (POD) activities were higher in all treated plants compared to those of CK, effectively removing O2− and providing H2O2 protection, thereby delaying plant senescence and demonstrating strong adaptability. Through membership function analysis, the plant’s tolerance levels at various positions around the PV panels ranked under panels > before panels > behind panels > CK. In conclusion, A. adsurgens demonstrated adaptability to environmental changes at PV power stations by modifying its growth characteristics and physiological traits. These findings provide scientific evidence for the ecological industrial use of PV power stations in desert regions and offer practical guidance for vegetation restoration and ecological construction around such stations.